2013
DOI: 10.1186/1742-9994-10-43
|View full text |Cite
|
Sign up to set email alerts
|

Genetic incompatibility drives mate choice in a parasitic wasp

Abstract: IntroductionAllelic incompatibility between individuals of the same species should select for mate choice based on the genetic make-up of both partners at loci that influence offspring fitness. As a consequence, mate choice may be an important driver of allelic diversity. A complementary sex determination (CSD) system is responsible for intraspecific allelic incompatibility in many species of ants, bees, and wasps. CSD may thus favour disassortative mating and in this, resembles the MHC of the vertebrate immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…The apparent preference in wasps to place male eggs could reflect inbreeding avoidance and/or a mechanism to reduced diploid male production. In some hymenopteran species with CSD, females will avoid mating with males that are genetically similar at the sex determination locus (Harper, Bagley, Thompson, & Linnen, ; Metzger, Bernstein, Hoffmeister, & Desouhant, ; Ruf, Dorn, & Mazzi, ; Thiel, Weeda, De Boer, & Hoffmeister, ). Consequently, premating mechanisms linked to low diversity (e.g., avoidance of genetically similar mates) could also explain the higher than expected frequency of unmated females.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent preference in wasps to place male eggs could reflect inbreeding avoidance and/or a mechanism to reduced diploid male production. In some hymenopteran species with CSD, females will avoid mating with males that are genetically similar at the sex determination locus (Harper, Bagley, Thompson, & Linnen, ; Metzger, Bernstein, Hoffmeister, & Desouhant, ; Ruf, Dorn, & Mazzi, ; Thiel, Weeda, De Boer, & Hoffmeister, ). Consequently, premating mechanisms linked to low diversity (e.g., avoidance of genetically similar mates) could also explain the higher than expected frequency of unmated females.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratory studies in Bracon brevicornis have reported an avoidance of mating with a partner harboring the same allele at the sl‐CSD locus (i.e., avoidance of matched matings; Thiel et al. ), and sib‐mating avoidance was observed in V. canescens (Metzger et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, the lack of mate discrimination in C. rubecula could explain the relatively high DMP observed in its field populations (de Boer et al 2012). Laboratory studies in Bracon brevicornis have reported an avoidance of mating with a partner harboring the same allele at the sl-CSD locus (i.e., avoidance of matched matings; Thiel et al 2013), and sib-mating avoidance was observed in V. canescens (Metzger et al 2010a). Such behaviors should reduce the DMP and thus lessens the production of unfit offspring (Parker 1983;Chuine et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many species of Hymenoptera have life histories that could accelerate this extinction vortex by increasing the probability of producing diploid males and of females mating with them. For instance, gregarious immature development may increase the probability of sib‐mating, and viability of diploid males along with monandry may lower the fitness of sib‐mated females as well as females mating with diploid males (Godfray, ; Thiel & Weeda, ; Thiel, Weeda, de Boer, & Hoffmeister, ; Zayed & Packer, ). This puts strong pressure on Hymenoptera with CSD to develop ways to decrease sib‐mating, for example, through behavioral mechanisms (Metzger, Bernstein, Hoffmeister, & Desouhant, ; Ode, Antolin, & Strand, ; Van Wilgenburg, Driessen, & Beukeboom, ).…”
Section: Introductionmentioning
confidence: 99%